PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK BAN MERK PRIMAX DI KOTA PEKANBARU - Lamin, Lamin (Eko dan Bisnis: Riau Economic and Business Review, 2018)
In this study data were collected through a questionnaire of 62 respondents who became consumers of PRIMAX brand tires in Pekanbaru. Then the analysis of the data obtained in the form of quantitative analysis. Based on the results of the research analysis found that the test results on the variable Price (X) on Purchase Decision (Y) can be seen that the t-count is greater than t-table (5.049> 2,000) with a significant level of 0.00 <0.05. It can be concluded that Price variable (X) has a positive and significant effect on Purchase Decision (Y) The result of simple linear regression shows Y = a + bX namely: Y = 25,144 + 0,607X. From the regression equation it is concluded that the regression coefficient of bx is positive. This shows the price variables if the increased equation will lead to an increase also in the variable of purchase management. R Square results of 0.389 (38.9%) explained that the purchase decision influenced the price by 38.9%